2020
DOI: 10.1101/2020.02.24.20027623
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spread and control of COVID-19 in China and their associations with population movement, public health emergency measures, and medical resources

Abstract: 20 BACKGROUND The COVID-19 epidemic, first emerged in Wuhan during December 2019, has 21 spread globally. While the mass population movement for Chinese New Year has significantly 22 influenced spreading the disease, little direct evidence exists about the relevance to epidemic and its 23 control of population movement from Wuhan, local emergency response, and medical resources in 24 China. fatality rate was 2.84%, much higher in Hubei than in other regions (3.27% vs 0.73%). The index of 29 population inflow f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 16 publications
4
15
0
Order By: Relevance
“…The best available scientific evidence is therefore required to design effective NPI strategies and disseminate this knowledge urgently to help policy makers assess the potential benefits and costs of NPIs to contain COVID-19 outbreaks. Some previous studies have preliminarily explored the lockdown of Wuhan, [25][26][27] travel restrictions, [28][29][30] airport screening, 31,32 and the isolation of cases and contact tracing for containing virus transmission, respectively. 33,34 The conclusions of these studies are persuasive, there are still key knowledge gaps on the effectiveness of different interventions.…”
Section: Introductionmentioning
confidence: 99%
“…The best available scientific evidence is therefore required to design effective NPI strategies and disseminate this knowledge urgently to help policy makers assess the potential benefits and costs of NPIs to contain COVID-19 outbreaks. Some previous studies have preliminarily explored the lockdown of Wuhan, [25][26][27] travel restrictions, [28][29][30] airport screening, 31,32 and the isolation of cases and contact tracing for containing virus transmission, respectively. 33,34 The conclusions of these studies are persuasive, there are still key knowledge gaps on the effectiveness of different interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was also the earliest date when systematic data for all provinces were available. In the second stage after February 2020, the number of covid-19 cases largely represents further local diffusion in various provinces and the number would be largely determined by the initial cases transferred from Hubei The spread of covid-19 is related to both the spatial configuration and the population flows between Wuhan and other provinces (Alirol et al 2010;Chen et al 2020;Ying et al 2020;Kraemer et al 2020). It may also be related to population and economic size of a province, population density, urbanization level, income level and economic growth rate (Coker et al 2011;Tong et al 2015;Wu et al 2017).…”
Section: Research Methodology and Datamentioning
confidence: 99%
“…They indicated that population movement might be one important trigger of covid-19 infection transmission in China. Ying et al (2020) conducted Spearman's correlation analysis between official data of confirmed covid-19 cases, and real-time travel data and health resources data for the period 20 January to 19 February 2020 for provinces and cities, reporting high correlation coefficients. Kraemer et al (2020) found positive correlation between the growth rate of covid-19 cases and the population flow from Wuhan in the period 9-22 January 2020.…”
Section: Introductionmentioning
confidence: 99%
“…However, we also see good examples like Shanghai, Fujian and Shanxi, which were able to reduce the growth rate consistently with a low variance. These provinces benefited from experience obtained in the fight against the 2003 SARS outbreak or enjoy richer local medical resources [34]. This enabled the government to identify as many infected/suspected cases as possible in order to contain continuously the local transmissions.…”
Section: Heterogeneity Of the Development Of The Epidemic And Responsmentioning
confidence: 99%